The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.3390/ph9030034
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Surface Properties and In Vitro Drug Release from a Compressed Matrix Containing an Amphiphilic Polymer Material

Abstract: The performance of compressed tablet drug delivery systems made using polymeric materials depend on multiple factors, such as surface properties like contact angle, surface free energy and water absorption rate, besides the release mechanisms driven by the kind of polymer used. Hence, it should be possible to establish a relationship between the surface properties and the drug release kinetics. Compressed tablets with different proportions of poly(maleic acid-alt-octadecene) potassium salt (0%, 10%, 20%, 30% a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 68 publications
5
20
0
Order By: Relevance
“…Furthermore, the data of disintegration time are also very interesting, for the PAM-4Na polymer, which is a hydrophilic low molecular weight material; the matrix disintegration is almost immediate and occurs in a similar way as a conventional release tablet; on the other hand, the PAM-18Na polymer is amphiphilic in nature and shows an increasing disintegration time, due to the high cohesiveness degree of the tablet. This result is quite similar to that obtained in a previous study, where a similar amphiphilic material was used, but with a potassium counter ion [ 27 ]. In contrast, the hydrophobic polymer PAM-18 showed a rapid disintegration attributed to the low hardness of the tablet; while the reference polymer HPMC showed higher values of disintegration time because such a matrix might swell in aqueous media forming gel-like structures that are difficult to disintegrate [ 21 ].…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Furthermore, the data of disintegration time are also very interesting, for the PAM-4Na polymer, which is a hydrophilic low molecular weight material; the matrix disintegration is almost immediate and occurs in a similar way as a conventional release tablet; on the other hand, the PAM-18Na polymer is amphiphilic in nature and shows an increasing disintegration time, due to the high cohesiveness degree of the tablet. This result is quite similar to that obtained in a previous study, where a similar amphiphilic material was used, but with a potassium counter ion [ 27 ]. In contrast, the hydrophobic polymer PAM-18 showed a rapid disintegration attributed to the low hardness of the tablet; while the reference polymer HPMC showed higher values of disintegration time because such a matrix might swell in aqueous media forming gel-like structures that are difficult to disintegrate [ 21 ].…”
Section: Resultssupporting
confidence: 90%
“…On the other hand, for tablets containing PAM-4Na, it is observed that increasing the amount of polymer leads to a slight and gradual increase of θ c . In the case when the tablets contain PAM-18Na, the results are very close to those previously found with a similar polymer, such as PAM-18K [ 27 ], where at polymeric proportions of 10% and 20%, θ c is much lower compared to the value shown by the surfaces of the ampicillin tablets, whereas at polymer proportions of 30% and 40%, θ c values are greater and very close to 90°, suggesting a transition from a hydrophilic to a hydrophobic surface.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Releasing efficiency was defined in terms of the mass flux ( J ) [ 21 , 22 ], which describes the change of drug permeation with respect to time in aqueous systems. In our study, the mass flux (mol·cm −2 ·h −1 ) was determined using the AUC of the permeation profile recorded at a specific time interval and is related to the rectangular area ( R ) described by 100% of the permeation process at the same time interval (24 h).…”
Section: Methodsmentioning
confidence: 99%
“…When n equals 0.5, the equation becomes equal to the Higuchi model, indicating that the release mechanism is of a Fickian type (case I), whereas values of n between 0.5 and 1.0 suggest that the release mechanism corresponds to an anomalous (non-Fickian) transport. Values of 1.0 indicate that the release mechanism is similar to a zero-order release, whereas values of n greater than 1.0 (Super Case II transport) suggest a drug release process dependent on the relaxation of the polymer chains in the matrix, passing from a vitreous state (lower kinetic movement and increased potential energy) to a relaxed state rubber type (high kinetic movement and lower potential energy) [ 22 , 27 ].…”
Section: Methodsmentioning
confidence: 99%